ANALISIS PERTANGGUNGJAWABAN OJK TERHADAP INVESTASI ONLINE BODONG BINOMO YANG DILAKUKAN INDRA KENZ DITINJAU DARI ASPEK YURIDIS - Maisa Aulia; Fenti Erdiana Efendi; Renata Tianggur Manurung (Peneliti.net, 2023)
Investment is considered effective by most people to manage personal assets. Fraudulent investments often occur in online investments that harm some individuals and can even pose a threat to the country's economy. An example is the case of the binomo platform and binary options trading. One of the binomo cases that was widely discussed was Indra Kenz, one of the binomo application affiliators. The existence of fraudulent investment cases like this indirectly proves that state institutions that have the authority to supervise do not carry out their functions thoroughly. The Financial Services Authority (OJK) should be able to carry out preventive measures for the many cases of fraudulent investment in Indonesia. The success of rogue investment providers is the main urgency so that no more such cases are found. Based on this normative research, results are obtained regarding the effectiveness of OJK's performance. In terms of complaints related to fintech violations during 2018-2020, there were 19,711, of which 47% were categorized as serious violations. In that time, OJK managed to take action against 3,516 complaints. It can be concluded that the supervision carried out by OJK and the regulations released by OJK are still not qualified to handle problems related to fintech complaints. In analyzing the Indra Kenz case, it is juridically reviewed that his actions are considered similar to the crime of money laundering so that he has been found guilty and subject to multiple article sanctions.